Insecticidal and antifeedant bioactivities of Melaleuca alternifolia essential oil on Ascia monuste orseis - Martins Da Silva, Paulo Henrique; Prado, Evandro Pereira; Ferreira-Filho , Pedro José; Francisco, João Paulo; Del Quiqui, Erci Marcos; Silva, Camila; Guerreiro, Julio César (Revista Colombiana de Entomología, 2023)
This study evaluated the bioactive effects of Melaleuca alternifolia essential oil on the behavior and mortality of Ascia monuste orseis caterpillars. The experiment was conducted at the laboratory under controlled conditions using a completely randomized design with six treatments, represented by A. monuste orseis caterpillars fed collard leaves treated with 0 (control), 5, 10, 20, 30, or 40 mg mL−1 essential oil. Each treatment consisted of five replicates of four third-instar caterpillars. Mean daily intake of collard leaves, feces production, mortality, and behavioral changes were assessed for 15 days after the beginning of the experiment. Data on leaf intake and feces production were subjected to analysis of variance by the F-test; when significant differences were found, data were subjected to regression analysis. Corrected mortality rate was calculated and subjected to analysis of variance by the F-test followed by Tukey’s test at the 5% significance level for comparison of means. The median lethal dose (LD50) was also evaluated. Two very clear feeding behaviors were observed, one in caterpillars exposed to essential oil concentrations of 5, 10, and 20 mg mL−1, which showed little difference in feed intake from the control, and the other in caterpillars exposed to the highest concentrations (30 and 40 mg mL−1), which showed a decrease of 76 to 93% in feed intake compared with the control. Lower leaf intake resulted in a decrease in feces production, and the negative effects increased linearly with essential oil concentration. The mortality curve showed a linear and positive response to essential oil concentration, reaching 100% in insects exposed to the highest concentrations. The LD50 was 13.93 mg mL−1.